Risk factors associated with diabesity in primary school students in the Amazon region of Brazil - Maria Virgínia Filgueiras de Assis Mello; Rosemary Ferreira de Andrade; Liudmila Miyar Otero; Anneli Mercedes Celis de Cárdenas; Silvana Rodrigues da Silva (Universidad de Antioquia, 2013)
Objective. Identifying risk factors for diabesity (diabetes plus obesity) in primary students in the Brazilian Amazon. Methodology. Descriptive study carried out in 2009 with the participation of 1218 students. A questionnaire from the Ministry of Health of Brazil was employed with the question ''How is your diet?'' and a form was created to record the socio-demographic, clinical, anthropometric and food variables. Results. The mean age was 12 years and 57% were female. 64% of respondents reported no health problems, 37% had a family history of diabetes mellitus and 29% of students were overweight (17% overweight and 12% obese). A sedentary lifestyle was prevalent in the study group (70%). The dietary guidelines for consumption of fruits, vegetables, legumes, and complex carbohydrates are not properly fulfilled. Fast foods or 'junk' food was consumed by 43.5% of students. Conclusion. Most of the identified risk factors were related to unhealthy lifestyles that can lead to diabesity and other chronic non-communicable diseases. Identifying these factors allows planning nursing interventions for students, teachers and families.